From victims and mothers to citizens: gender-just transformative reparations and the need for public and private transitions - Weber, Sanne (International journal of transitional justice, 2018)
Colombia’s 2011 Victims’ Law is often seen as an example of best practice in transitional justice, combining land restitution and individual and collective reparations. This law builds on the increasingly popular concept of transformative reparations and moreover prescribes a ‘differential focus’ to guarantee the inclusion and protection of groups considered to be especially vulnerable. Based on nine months of ethnographic and participatory visual fieldwork in two villages in Colombia’s Caribbean coast, this article discusses how this ‘differential focus’ plays out in practice by critiquing the way in which it is based on a highly essentialized and narrow understanding of gender. Based on the experiences and ideas of women involved in the Victims’ Law process, the article suggests how a focus on citizenship could offer a new approach to reparations, with more potential for transforming gender inequality.